THE WELL-BEING OF JOINT MINOR CHILDREN AS A NEGATIVE PREMISE FOR DIVORCE. THE PROBLEM OF ECONOMIC ABANDONMENT OF A CHILD - Chrząścik, Marcin; Szponar, Oliwia; Ratowski, Tomasz (Management and Administration Journal, 2024)
The principle of protecting the best interests of the child is a key element of modern family law, balancing the interests of spouses with the needs and rights of minors. The Constitution of the Republic of Poland and the provisions of family law impose the obligation to protect the rights of the child, which translates into court practice. The concept of ‘best interests of the child” is difficult to define, but constitutes an overriding interest that is the basis of legal proceedings in family matters, especially divorce cases. One of the main topics discussed in this article is the discussion of the premise of the inadmissibility of a divorce decision for the sake of the minor children. The court must make the right decisions, considering both the best interests of the children and the needs of the parents. Arguments are also cited about the potential negative effects of divorce on children. The discussed content also touches on the topic of maintenance payments and the problem of nonpayment of child support, which is defined as economic abandonment of a minor. The analysis includes a review of the literature in the field of various social sciences.